(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2020)
The research aims to identify the factors affecting the customer and their impact desire for market share in a competitive market National Insurance Company, where he was after the tremendous developments that have taken place in the insurance sector, crowded markets, private companies and the intensified competition among those companies on one side and public sector companies, including national insurance company on the other hand, increased attention and study in a big way the customer and the factors influencing the desire. As the national insurance company ascertains its targets once the sale of insurance documents only, but by knowing the tendencies and aspirations of current and prospective customers a way that helps to strengthen the competitive position and increase competitiveness, so that the study process and analyze the factors affecting the desire of the customer has become the goal sought by the company and that because this desire to affect significantly the marketing of company documents and assist them in selling policy and make it easier to plan and make decisions related to marketing activity and the achievement of the objective to increase the market share of the company process. To achieve the objectives of the study and testing of hypotheses designed a questionnaire for the purposes of research and investigation is made up of 90 form in three different places in the national insurance company where results showed that customer’s desire to effect a significant market share in the National Insurance Company.